구미 남부 금오산 칼데라의 함몰 유형과 과정 - 황상구(Sang Koo Hwang); 손영우(Young Woo Son); 서승환(Seung Hwan Seo); 기원서(Weon-Seo Kee) (자원환경지질, 2021)
The Gumi basin, situated in the mid-southeastern Yeongnam Massif, has the Cretaceous stratigraphy that is divided into Gumi Formation, andesitic rocks (Yeongamsan Tuff, Busangni Andesite), rhyolitic rocks (Obongni Tuff, Doseongul Rhyolite, Geumosan Tuff) and Intrusives (ring dikes, other dikes) in ascending order. The Geumosan Tuff is composed mostly of many ash-flow tuffs which are associated with Geumosan caldera along with the ring dikes. The caldera is outlined by ring faults and dikes and has about 3.5 × 5.6 km in diameters. The intracaldera volcanics show a downsag structure that is dipped inward in their flow and welding foliations. The caldera block represent an asymmetric subsidence, which drops 350 m in the northern margin and 600 m in the southern one. Based on these data, the Geumosan caldera is geometrically classified as an asymmetric piston subsidence caldera that suggests a single caldera cycle. The caldera reflects the piston subsidence of the caldera block bounded by the outward-dipping ring faults following a voluminous eruption of magma from the chamber. The downsag in the caldera block refers to the downsagging during the initial subsidence at the same time as the full development of the bound fault. In the ring fissures following the sagging, magma was injected due to the overpressure of magma chamber caused by subsidence. 구미분지는 영남육괴의 남동 중간부에 있으며 하부로부터 백악기의 구미층, 안산암질암류(영암산응회암, 부상리안산암), 유문암질암류(오봉리응회암, 도선굴유문암, 금오산응회암)와 관입암류(환상암맥, 기타 암맥)로 구성된다. 금오산응회암은 거의 대부분 회류응회암으로 구성되며 환상암맥과 함께 금오산 칼데라와 연관되어있다. 칼데라는 직경이 3.5 × 5.6 km이고 환상암맥과 단층으로 둘러싸인다. 칼데라 내부 화산암층은 유상 및 용결엽리가 대체로 칼데라 연변부에서 안쪽으로 경사되는 하향자루 구조를 나타낸다. 칼데라 블록은 북변부에서 350m, 남변부에서 600m 내려앉은 비대칭 침하를 나타낸다. 이 자료들에 의하면 금오산 칼데라는 하나의 칼데라윤회를 암시하는 기하학적으로 비대칭 피스톤 침하 칼데라로 분류된다. 이 칼데라는 챔버로부터 마그마의 대규모 분출에 뒤따라 외측경사 환상단층으로 경계되는 칼데라 블록의 피스톤 침하를 지시한다. 칼데라 블록에서 하향자루는 경계 단층의 완전한 발달과 동시에 초기 침하동안 하향자루운동을 의미한다. 이 운동에 의한 벌어진 환상열극에는 침하에 따른 마그마 과압으로 인해 마그마가 주입되어 환상암맥을 형성하였다.